Principal Strategic Management in Enhancing Teacher Professionalisme at MAN 3 Langkat - Muhammad Riski Syahputra; Mhd. Fuad Zaini Siregar; Yuria Nadila (Pusdikra-Publishing.com, 2023)
Education is a conscious and planned effort aimed at creating a conducive learning environment and processes for students to actively develop their potential, encompassing spiritual strength, self-control, personality, intelligence, noble character, and essential skills for themselves, society, the nation, and the state. This research explores the strategic management of school principals in enhancing teacher professionalism at MAN 3 Langkat. The qualitative research method, employing a phenomenological approach, is chosen to deeply understand natural phenomena related to school principal strategies in improving teacher professionalism. The findings reveal several strategies used by the school principal, such as intensifying meetings, effective teacher duty rotation, sending teachers to workshops, and offering guidance and supervision. The school principal's enthusiasm for improving teacher professionalism is evident through professional training and active involvement in problem-solving. In conclusion, the school principal's strategic management significantly contributes to enhancing teacher professionalism at MAN 3 Langkat. This research underscores the importance of collaboration between school principals and teachers, sharing a common vision, mission, and goal in achieving educational objectives. It emphasizes the continuous professional development of teachers to optimize their potential and deliver high-quality education.